Leber hereditary optic neuropathy in Czechia and Slovakia: Quality of life and costs from patient perspective - Bušányová, Beáta; Vajter, Marie; Kelifová, Silvie; Lišková, Petra; Miková, Hedviga; Breciková, Katarína; Žigmond, Ján; Rogalewicz, Vladimír; Tichopád, Aleš; Višňanský, Martin; Šarkanová, Ivana (Heliyon, 2024)
INTRODUCTION: Leber hereditary optic neuropathy (LHON) is the most frequent mitochondrial disease causing dyschromatopsia and progressive central visual loss that is subacute in progression and painless. Several studies have been published assessing QoL in patients with LHON, but no estimate of the economic burden has been reported to date. This study aims to quantify direct non-medical and indirect costs (productivity loss) incurred by LHON patients and their informal caregivers in Czechia and Slovakia, as well as to assess their quality of life. METHODS: The study was performed in 27 adults and children with LHON. To determine the socioeconomic burden of LHON, separate questionnaires for adults, children, and their parents were developed, including demographic and socioeconomic data. The following data were collected: age, education, family size, severity of LHON, non-medical direct and indirect costs of LHON. RESULTS: The mean age of adult respondents was 36.1 years (SD 13.1; n = 21). The total cost of absenteeism was EUR 1003 per person/year in adult employees, and EUR 2711 per person/year in children's parents. The productivity loss as a consequence of LHON due to combined relative absenteeism and relative presenteeism was estimated at EUR 9840 per an adult patient/year, and EUR 6298 per a parent/year, respectively. The mean cost of informal care was estimated at EUR 4502 (SD 4772; n = 6) per person/year. The mean VFQ-25 score for adult patients with LHON was 43.47 (SD 15.86). CONCLUSION: The results of this study clearly show that patients with LHON and their families face an extensive socioeconomic burden related to this rare disease. Early, timely and appropriate access to diagnosis, treatment, and reimbursement decisions, but also to psychological counselling and services may help the patients and their relatives adapt and cope with the challenging aspects of vision loss and life with the disease.
Keywords: Quality of life; Productivity loss; Socioeconomic burden; LHON; Absenteeism